STUDENTS’ PERCEPTUAL ENGLISH LEARNING STYLE; MAJOR AND MINOR PREFERENCES IN HIGHER EDUCATION - Arif, Muhammad; Danial, Muhammad; Nurhaeni, Nurhaeni (LLT Journal: A Journal on Language and Language Teaching, 2021)
Every students have different ways in collecting, processing, and understanding information. Those refers to the preferences of students in learning or known as learning styles. Therefore, this study aimed to identify and recognize the students’ major and minor perceptual learning style preferences in English Education Department at Universitas Sulawesi Barat. This research was used quantitative approach by using survey design. This research was conducted in English Education Department at Universitas Sulawesi Barat with 79 respondents or college students who were selected by Saturated sampling. The data of this research were collected by using Reid’s (1987) Perceptual Learning Style Preferences Questionnaire (PLSPQ). The data were analysed with self-scoring based on Reid (1978) and descriptive statistic by using SPSS Software Statistic Version 20. The findings of the research shows the averages of the learning style of college students in English Education Department at Universitas Sulawesi Barat the year 2019 was categorized as none major perceptual learning styles preference. On the other hand, they were categorized as minor perceptual learning styles preference, in which kinaesthetic learning style had highest mean with (37.84) than another learning style, and followed by group learning style with mean (37.67), tactile with mean (36.91), auditory with mean (36.55), visual with mean (35.87), and individual learning style with mean (34.73). Even though they were categorized as minor perceptual learning styles preference, but the students still be able to learn better by their high minor condition.